Hegemomoni Epistemologi Post-Modernisme Filsafat Ilmu terhadap Penafsiran Al-Qur’an - Arjuna, Klawing; Supriyanto, Supriyanto (Institut Agama Islam Sumatera Barat, 2023)
This article aims to find common ground between modern and postmodern philosophy in interpreting the Quran, and to explore how the epistemology of postmodern philosophy influences Quranic interpretation. Using a qualitative descriptive research method, the article seeks to identify the impact of postmodern epistemology on Quranic interpretation. The findings reveal that postmodern philosophy does not oppose modern philosophy, but rather seeks to correct and guide and corrects modern philosophy. Postmodernism highlights the compatibility between modern and postmodern philosophies, and how they can be integrated to gain a more comprehensive understanding. Furthermore, the article also examines the hegemony of postmodern epistemology on Quranic interpretation, which is not a rejection of modern interpretation. Instead, it can be seen as an alternative perspective that explores postmodern values as a continuation of modern values. Postmodernism suggests that Quranic interpretation can be integrated with postmodern philosophy without erasing the essential values of the preceding modern era.